Automatic Morphological Processing in Middle School Students with and without Word Reading Difficulties - Leah M. Zimmermann; Derek B. Rodgers; Bob McMurray (MDPI AG, 2024)
Morphological processing is the use of morphological structure during word reading. This study investigated whether middle school students applied morphological structure automatically when reading words. In addition, this study asked whether students with word reading difficulties (WRD) applied morphological structure in a way that differed from proficient word readers. Participants were seventh- and eighth-grade students (n = 80). Students were divided into two reading ability groups: proficient word readers (n = 55) and students with word reading difficulties (n = 25). Four computer-administered experimental tasks measured automaticity in reading morphologically complex words and morphologically simple words. A backward masking measure assessed whether students were applying morphological structure automatically to support task accuracy. Students were significantly more accurate in masked performance with morphologically complex words than with morphologically simple words on an oral word reading task. Students with WRD benefitted more from morphological structure on this task than proficient readers did. Findings suggest that proficient word readers and students with WRD automatically apply morphological structure when reading words aloud. In addition, middle school students with WRD may rely more on morphological structure than their proficient peers. However, there may be differences in morphological processing based on the nature of word reading tasks.